Shari'ah governance in Islamic banks: practices, practitioners and praxis - Dewi, Fatmawati; Mohd Ariffin, Noraini; Zainal Abidin, Nor Hafizah; Osman@Hussin, Ahmad Zamri (Elsevier Ltd, 2020)
This study examines Shari'ah governance in Islamic banks by analyzing and comparing international and national Shari'ah governance codes across 11 countries and the annual reports of the largest stand-alone Islamic bank in each of these countries. Drawing upon the practice theory framework, this study identifies the similarities and differences across countries in Shari'ah governance practices, practitioners, and praxis. Regarding practices, we found that the 11 countries reviewed have adopted different approaches, i.e., strict, moderate, or flexible approaches, in developing regulations for Shari'ah governance structures and processes. The approach taken by each country, in turn, influences Shari'ah governance practitioners and praxis at the institutional level to some extent. Specifically, Islamic banks in countries belonging to the moderate and flexible groups are likely to be more varied in terms of Shari'ah governance practitioners as well as praxis (activities or processes) to ensure Shari'ah compliance as compared to their counterparts in countries with strict regulations. Analyzing current Shari'ah governance practices in 11 countries may promote a greater understanding of the critical issues and gaps that arise each different context. Therefore, the findings of this study can provide relevant information for both regulators and practitioners to further improve the Shari'ah governance model and best practices in the Islamic banking industry.